A Preliminary Test of Novelty-Facilitated Extinction in Individuals With Pathological Anxiety - Steinman, Shari A.; Dunsmoor, Joseph E.; Gazman, Zhamilya; Stovezky, Yael; Pascucci, Olivia; Pomerenke, Justin; Phelps, Elizabeth A.; Fyer, Abby; Simpson, H. Blair (Frontiers in Behavioral Neuroscience, 2022)
Studies with rodents and healthy humans suggest that replacing expected threat with a novel outcome improves extinction and reduces return of conditioned fear more effectively than threat omission alone. Because of potential clinical implications of this finding for exposure-based anxiety treatments, this study tested whether the same was true in individuals with pathological anxiety (i.e, met DSM-5 diagnostic criteria for an anxiety disorder and/or obsessive-compulsive disorder (OCD). In this preliminary test of novelty-facilitated extinction, fifty-one unmedicated individuals with pathological anxiety were randomized to standard extinction (n=27) or novelty-facilitated extinction (n=24). Participants returned 24 hours later to test extinction recall and fear reinstatement. Skin conductance responses (SCR) were the dependent measure of conditioned fear. Participants in both groups learned the fear association but variably extinguished. Novelty did not facilitate extinction in this preliminary trial. Findings underscore the importance of translating paradigms from healthy humans to clinical samples, to ensure that new treatment ideas based on advances in basic neuroscience are relevant for patients.